2002
DOI: 10.1046/j.1365-4362.2002.01596.x
|View full text |Cite
|
Sign up to set email alerts
|

The genetic epidemiology of psoriasis vulgaris in Chinese Han

Abstract: Psoriasis vulgaris follows a pattern of polygenetic or multifactorial inheritance rather than single-gene inheritance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 14 publications
5
51
1
Order By: Relevance
“…Psoriasis is a complex and polygenetic hereditary disease involving genetic risk factors and environmental triggers, and the former usually play decisive roles in the pathogenesis and mechanism of psoriasis [2][3][4]21] . Therefore, it is of great significance to screen and clarify the function of more genetic risk factors or PSORS genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psoriasis is a complex and polygenetic hereditary disease involving genetic risk factors and environmental triggers, and the former usually play decisive roles in the pathogenesis and mechanism of psoriasis [2][3][4]21] . Therefore, it is of great significance to screen and clarify the function of more genetic risk factors or PSORS genes.…”
Section: Discussionmentioning
confidence: 99%
“…The research progresses on genetic epidemiology, and genetics have confirmed that psoriasis is a complex and polygenetic hereditary disease mediated by the cells and molecules of both the innate and adaptive immune systems [2] , and its possible pathogenesis and mechanism consist of the interaction between gene and gene and between gene and environment (stress, trauma, environmental pollution, etc.) [3,4] . Therefore, clarifying the functions of psoriasis susceptibility genes is of great significance for the treatment of psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…The heritability of psoriasis was 71% in first degree relatives and 37% in second degree relatives. 26 …”
Section: Risk Factors Geneticsmentioning
confidence: 99%
“…The mean age at diagnosis has been reported to be between 10 and 11 years of age by a recent large population-based study [ 13 ]. Onset may occur slightly earlier for females [ 14 ], although studies have shown nearly equal male to female prevalence ratios [ 11 , 12 , 15 ]. Onset may also occur earlier in those with a positive family history of psoriasis [ 14 ].…”
mentioning
confidence: 99%
“…Onset may occur slightly earlier for females [ 14 ], although studies have shown nearly equal male to female prevalence ratios [ 11 , 12 , 15 ]. Onset may also occur earlier in those with a positive family history of psoriasis [ 14 ]. Table 20.1 shows a review of worldwide presentation of pediatric psoriasis.…”
mentioning
confidence: 99%